CSS Basics for Styling A Web Content - Sharma, Manish Kumar; Bhardwaj, Rama; Singh, Abhiyendra; Gaur, Kartik Singh (International Journal of Psychosocial Rehabilitation, 2020)
In this research paper I’ll explain that how to use cascading style sheet (CSS) to make a website look good. CSS is like the designer for the websites. It mainly uses in website and help to create or change colors, font and layouts to making site more attractive. Therefore, in this paper we break CSS into normal east steps, so each and every beginner can understand properly. Now we show you that how to pick elements on site like-paragraphs or headings and then how they look. By end of this research paper you will know about the basics of CSS and how to create web content stylish.